Archéologie de la Bible hēbraïque: culture scribale et Yahwismes - Lemardelé, Christophe (Archaeopress Publishing Ltd, 2019)
Since the Renaissance, the question of how the Bible was written has been much debated. Documentary theory of the end of the 19th century identified 'authors' and schools of writing, paving the way so that, a century later, a complex reality emerged, that of scribes modifying texts as they copied them. Thus, 'The Bible' no longer appears as a controlled theological and historiographical project but as the empirical arrangement of heterogeneous texts linked together by an evolving religious ideology. While the first books are based on the election and migration of an entire people, the ideological foundations of Yahwism evoke rather a foreign god who, having reached Israelite territory, ultimately gained pre-eminence there. This monotheistic ideology was above all an exclusivism that was to be reinforced from the time of the kings of Israel